Halal Certification Priorities for Indonesian MSEs: A Comparison Between Stakeholder Perspectives and AI-Based Insights - Priantina, Anita; Sapian, Safeza Mohd; Shafii, Zurina; Ibrahim, Norhazlina (Jurnal Ar-Ribh, 2025)
The implementation of mandatory halal certification in Indonesia poses significant challenges for Micro and Small Enterprises (MSEs), primarily due to constrained financial, technical, and human resources, as well as complex regulatory frameworks. This study investigates strategic priorities to support MSEs in navigating the halal certification process by juxtaposing qualitative perspectives from key halal ecosystem stakeholders government officials, certification bodies, MSE practitioners, and halal influencers with insights generated through artificial intelligence (AI). Employing content and thematic analysis, the study addresses the core research question: “What should be prioritized to facilitate halal certification for Indonesian MSEs?” The findings highlight both areas of convergence and divergence between human and AI-generated perspectives, particularly concerning the practicality, scalability, and sustainability of proposed interventions. While stakeholders emphasize the need for institutional support, simplified procedures, and capacity building, AI contributes innovative, data-driven strategies such as automated compliance tools and targeted digital outreach. This integrative analysis offers a novel contribution by bridging human-centric knowledge with AI-enabled foresight, thereby informing evidence-based policymaking and operational strategies. Ultimately, the study provides a multidimensional roadmap for enhancing the accessibility, efficiency, and inclusivity of halal certification in Indonesia, particularly for MSEs that constitute a vital segment of the national economy and halal value chain.